Isolation of xylanolytic multi-enzyme complexes from Bacillus subtilis SJ01 - Jones, Sarah Melissa Jane (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2010)
Cellulose and hemicellulose account for a large portion of the world's plant biomass. In nature, these polysaccharides are intertwined forming complex materials that require multiple enzymes to degrade them. Multi-enzyme complexes (MECs) consist of a number of enzymes working in close proximity and synergistically to degrade complex substrates with higher efficiency than individual enzymes. The cellulosome is a cellulolytic MEC produced by anaerobic bacteria that has been studied extensively since its discovery in 1983. The aim of this study was to purify a cellulolytic and/or hemicellulolytic MEC from an aerobic bacterium of the Bacillus genus. Several bacterial isolates were identified using morphological characteristics and 16S rDNA sequencing, and screened for their ability to degrade cellulose and xylan using a MEC. The isolate that produced a high molecular weight protein fraction with the greatest ability to degrade AvicelÂ®, carboxymethyl cellulose (CMC) and birchwood xylan was identified as Bacillus subtilis SJ01. An optimised growth medium, consisting of vitamins, trace elements, birchwood xylan (as the carbon source), and yeast and ammonium sulphate (as the nitrogen sources), increased the production of CMCase and xylanase enzymes from this bacterium. The removal of a competing bacterial strain from the culture and the inhibition of proteases also increased enzyme activities. A growth curve of B. subtilis SJ01 indicated that xylanase production was highest in early stationary growth phase and thus 84 hours was chosen as the best cell harvesting time. To purify the MECs produced by B. subtilis SJ01 size-exclusion chromatography on a Sephacryl S-400 column was used. It was concluded that (for the purposes of this study) the best method of concentrating the culture supernatant prior to loading onto Sephacryl S-400 was the use of ultrafiltration with a 50 kDa cut-off membrane. Two MECs, named C1 and C2 of 371 and 267 kDa, respectively, were purified from the culture supernatant of B. subtilis SJ01. Electrophoretic analysis revealed that these MECs consisted of 16 and 18 subunits, respectively, 4 of which degraded birchwood xylan and 5 of which degraded oat spelt xylan. The MECs degraded xylan substrates (C1: 0.24 U/mg, C2: 0.14 U/mg birchwood xylan) with higher efficiency than cellulose substrates (C1: 0.002 U/mg, C2: 0.01 U/mg CMC), and could therefore be considered xylanosomes. Interestingly, the MECs did not bind to insoluble birchwood xylan or AvicelÂ® and did not contain glycosylated proteins, which are common features of cellulosomes. This study is, therefore, important in revealing the presence of MECs that differ from the cellulosome and that may have particular application in industries requiring high xylanase activity, such as the paper and pulp industry. The abundant genetic information available on B. subtilis means that this organism could also be used for genetic engineering of cellulolytic/hemicellulolytic MECs.
Keywords: Bacillus subtilis; Xylans; Multienzyme complexes; Botanical chemistry; Cellulose; Hemicellulose; Polysaccharides